Ius Constituendum Kewenangan Judicial Preview di Mahkamah Konstitusi Republik Indonesia - Wada, Igam Arya; Kurniawan, Felix Alexander; Sinta, Agnes (Department of Constitutional Law, Faculty of Law, University of Jember, Indonesia, 2023)
Menurut Pasal 24C ayat (1) UUD 1945, Mahkamah Konstitusi memiliki wewenang salah satunya menguji konstitusionalitas undang-undang atau judicial review. Akan tetapi, buruknya kualitas legislasi dan intensitas perkara judicial review yang tinggi tidak diimbangi dengan kewenangan Mahkamah Konstitusi yang memadai. Dalam kapasitasnya sebagai negative legislator, Mahkamah Konstitusi Republik Indonesia tidak diperlengkapi dengan wewenang untuk menguji konstitusionalitas rancangan undang-undang atau judicial preview sebagaimana yang ada dalam negara Perancis, Jerman, Austria, Hungaria, dan lain-lain. Diadopsinya kewenangan judicial preview dalam Mahkamah Konstitusi Republik Indonesia merupakan upaya preventif kelemahan-kelemahan dari judicial review. Eksistensinya dapat meminimalisir undang-undang yang berkualitas buruk, meningkatkan perlindungan hak-hak konstitusional warga negara, mengantisipasi undang-undang berumur pendek, mencegah ketidakpastian hukum, meminimalisir penundaan perkara di Mahkamah Agung untuk peraturan perundang-undangan di bawah undang-undang yang memiliki relevansi dengan undang-undang yang sedang diujikan ke Mahkamah Konstitusi, mengantisipasi pembangkangan (constitutional disobedience) Dewan Perwakilan Rakyat sebagai lembaga adressat putusan Mahkamah Konstitusi, serta mengakomodir partisipasi publik. Hasil penelitian menunjukkan urgensi amandemen kelima Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 khususnya Pasal 24C ayat (1), serta perubahan keempat Undang-Undang Mahkamah Konstitusi dan Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan jo Undang-Undang Nomor 15 Tahun 2019 tentang Perubahan Atas Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan.Kata Kunci: Judicial Preview; Constitutional Disobedience; Pengujian Undang-Undang. According to Article 24C paragraph (1) of the 1945 Constitution, the Constitutional Court has the authority of one of them to test the constitutionality of the law or judicial review. However, the poor quality of legislation and the high intensity of judicial review cases are not balanced with adequate constitutional court authority. In its capacity as a negative legislator, the Constitutional Court of the Republic of Indonesia is not equipped with the authority to test the constitutionality of the draft law or judicial preview as it exists in France, Germany, Austria, Hungary, and others. The adoption of judicial preview authority in the Constitutional Court of the Republic of Indonesia is an effort to prevent the weaknesses of judicial review. Its existence can minimize poor quality laws, improve the protection of citizens' constitutional rights, anticipate short-lived laws, prevent legal uncertainty, minimize delays in cases in the Supreme Court for laws that have relevance to the law being tested to the Constitutional Court, anticipating constitutional disobedience the House of Representatives as an institution adressat the decision of the Constitutional Court, as well as accommodating public participation. The results of the study showed the urgency of the fifth amendment of the Constitution of the Republic of Indonesia year 1945 specially for Article 24C paragraph (1), as well as the fourth amendment of the Constitutional Court Law and Law No. 12 of 2011 on the Establishment of Legislation jo Law No. 15 of 2019 on Amendments to Law No. 12 of 2011 on the Establishment of Laws and Regulations jo Law No. 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning the Establishment of Laws and Regulations.Keywords: Judicial Preview; Constitutional Disobedience; Law Testing.